2021
DOI: 10.1038/s41421-021-00244-7
|View full text |Cite
|
Sign up to set email alerts
|

The first Conus genome assembly reveals a primary genetic central dogma of conopeptides in C. betulinus

Abstract: Although there are various Conus species with publicly available transcriptome and proteome data, no genome assembly has been reported yet. Here, using Chinese tubular cone snail (C. betulinus) as a representative, we sequenced and assembled the first Conus genome with original identification of 133 genome-widely distributed conopeptide genes. After integration of our genomics, transcriptomics, and peptidomics data in the same species, we established a primary genetic central dogma of diverse conopeptides, ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 64 publications
(127 reference statements)
3
43
0
Order By: Relevance
“…In our case, the inclusion of C. consors led to a significant decrease in the number of shared SOGs and influenced the following phylogenetic inference. This might be caused by the fragmentation and incomplete assembly of C. consors (scaffold N50 = 1,128 bp) ( Andreson et al, 2019 ), which in future studies can be replaced with the newly published chromosome level genome of cone snails, such as Conus betulinus Linnaeus, 1758 ( Peng et al, 2021 ) and Lautoconus ventricosus Gmelin, 1791 ( Pardos-Blas et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the inclusion of C. consors led to a significant decrease in the number of shared SOGs and influenced the following phylogenetic inference. This might be caused by the fragmentation and incomplete assembly of C. consors (scaffold N50 = 1,128 bp) ( Andreson et al, 2019 ), which in future studies can be replaced with the newly published chromosome level genome of cone snails, such as Conus betulinus Linnaeus, 1758 ( Peng et al, 2021 ) and Lautoconus ventricosus Gmelin, 1791 ( Pardos-Blas et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to compare 3,289 differentially expressed transcripts with the genome annotation data of C. betulinus, we downloaded the EST data (ID: PRJNA290540) associated with the article (Peng et al, 2021) and compared it through BLASTN. The threshold value is set to 1e-5.…”
Section: Differentially Expressed Genes Between Venom Bulb and Venom ...mentioning
confidence: 99%
“…To the best of our knowledge, an in-depth comparison of conopeptides among individual Conus caracteristicus, a vermivorous species, has yet to be performed. Furthermore, it is interesting that previous studies have identified hundreds of unique toxins or conopeptides from a single Conus specimen using genomic or proteomic methods (Biass et al, 2009;Davis et al, 2009;Kaas et al, 2010;Lavergne et al, 2015;Peng et al, 2021). Besides the diversity on gene or protein sequence level, the high toxin diversity is attributed to the oxidative folding of proteases in the venom (Buczek et al, 2005;Bulaj and Olivera, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Advanced omics along with bioinformatic tools are efficient approaches for high-throughput prediction of bioactive peptides such as AHTPs, toxins (Gao et al, 2018;Peng et al, 2021), antimicrobial peptides (Chen et al, 2020) and anticancer peptides (Zhong et al, 2020). In this study, we predicted some ATHP-rich proteins in the lined seahorse, especially those with high expression by integration of genome, transcriptome, and proteome data.…”
Section: Omics For High-throughput Ahtp Predictionmentioning
confidence: 99%